Comparison of mechanically ventilated patients with three types of - Farahani Borzabadi, ziba; Joodaki, maryam; Ashktorab, tahereh; Zaeri, farid; Atashzadeh Shurideh, froozan (Advances in Nursing & Midwifery, 2013)
ABSTRACT Background and aim : Communication is one of the most essential needs of human beings.Mechanical ventilation compromises patients’ ability to communicate their needs. This research was conducted to assess the effect of three methods of communication with patients receiving mechanical on their satisfaction in Arak hospitals 1389(2010). Method and materials : This randomized clinical trial was conducted in Intensive Care Units of Valey Asr, Amir Al Momenin and Ghods hospitals in Arak ,Iran. 60 patients who were admitted in ICU and were receiving mechanical ventilation were included in the study. These patients were randomly allocated in three groups.During a 12 hours period researcher used 1 method of communication for each group of these patients. These mrthods of communication included :A: Communicational board (words & letters). B: Communicational board (pictures & letters). C: The conventional method. Data were collected using a questionnaire. The questionnaire consisted of three parts: demographic variables, medical history and satisfaction with communication method.Validity of the instrument was assured by content validity index. , Cronbach’s alpha was used to determine the reliability of the iinstrument. SPSS, version 16 was used for data analysis. Findings: There was not a significant difference among three groups in terms of age, gender, mean length of stay in the ICU before mechanical ventilation treatment. The mean satisfaction scores were 2.58, 3.83 and 4.10 for conventional communication group, communication board A ( words & letters) and communication board B( pictures and letters) respectively. There was a significant difference among three groups in terms of their satisfaction with communication method (P<0.001).The one way analysis of variance indicated that using communication boards A & B significantly increased patient satisfaction. Conclusion: Using communication boards facilitates communication with mechanically ventilated patients and increase their satisfaction. * Corresponding Author: Ziba Farahani Borzabadi, Borzabadi Farahani. Dept.of Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Tehran, Iran Email: ziba_farahani_2000@Yahoo.com -Cabe C (2004). Nurse – patient communication: an exploration of patient’s experiences. Journal of Clinical Nursing.13(1) 41-49. -Elder N et al. (2008). Nurse’s perception of error communication and reporting in intensive care unit. Journal of Patient Safety. 4 (3)162-168. -Ghamari zare A et al (2008) [Quality of nurse’s performance and patient’s satisfaction in cardiac care units]. Tabib e Shargh Journal 10 (1) 27-36. (Persian) -Imani-Pour M [Quasi experimental research on anxiety and satisfaction of patients undergoing open cardiac surgery having intubation in selective hospital of Tehran Medical university 2001] MSc Thesis in nursing. Tehran University of Medical Science.(Persian) -Kozier B et al (2008). Fundamental of Nursing Concept and Procedure. 8th edition. New Jersey: Prentice-Hall. Inc. -Patak L Gawlinski A Fung I et al (2006) Communication boards in critical care: patients’ views.Applied Nursing Research 19(4) 182-190 -Potter P Perry A (2005). Fundamental of Nursing.7 th edition. St.Louis: Mosby. -Price A (2004). Intensive care nurses’ experiences of assessing and dealing with patient’s psychological needs. Nursing in Critical Care. 9(3):134-142. -Rask MT et al (2009). Effects of an intervention aimed at improving nurse-patient communication in an oncology outpatient clinic. Cancer Nursing.32 (1)1-11 -Schulmeister L et al (2005). Quality of life quality of care, and patient satisfaction: Perceptions of patient undergoing outpatient autologous stem cell transplantation. Oncology Nursing Forum. 32 (1) 57-59 -Stovesky B et al. (1988). Comparison of two types of communication methods used after cardiac surgery with patients with endotracheal tubs. Heart& Lung.17 (3) 281-289. -Taylor C Lillis C Lemone P (2008).Fundamental of Nursing: The Art and Science of Nursing Care. 6 th edition. Philadelphia: Lippincott. Co -Trovo De Araujo M Paes Da Silva M (2004). Communication with dying patient –perception of intensive care units nurses in Brazil. Journal of Clinical Nursing. 13 (5) 143-153.